A influência do pensamento moderno urbanístico no Centro Histórico de Cuiabá-MT - Garcia, Danielle Ferraz (2022)
Cities have undergone several transformations over the years and are a physical reflection of the various forms of interaction between man and the environment, although they are not designed in a way that promotes the integration of uses, classes and activities, being still, for the most part, , the result of an archaic and backward urbanization, translated into spaces that are not treated in a democratic way. Studying the relationship between cities, the environment, man and culture is fundamental to understand the past and the future, as the cultural field brings important contributions to be explored, since cities are the stage where cultural relations unfold and serve, therefore, as a basis for the phenomena of culture to take place. In this context, the general objective is to understand the influence of modern urban thinking in the Historic Center of Cuiabá, more precisely in the stretch between Avenida Getúlio Vargas to Rua Campo Grande, covering Rua Pedro Celestino, Calçadão Eng. Ricardo Franco and Boardwalk Eng. Galdino Pimentel. As specific objectives, we sought to interrelate the perception and vision of different agents involved with the center, such as specialists, owners, tenants and passers-by, aiming to sew urbanism with the social relations present there. Regarding the methodology used, a bibliographic review was used on the central themes of the research, as well as qualitative studies and interviews using the conversation method.